2008
DOI: 10.1007/s00415-008-0025-5
|View full text |Cite
|
Sign up to set email alerts
|

Preserved decision making ability in early multiple sclerosis

Abstract: BACKGROUND: The purpose of this study was to assess decision making in patients with multiple sclerosis (MS) at the earliest clinically detectable time point of the disease. METHODS: Patients with definite MS (n = 109) or with clinically isolated syndrome (CIS, n = 56), a disease duration of 3 months to 5 years, and no or only minor neurological impairment (Expanded Disability Status Scale [EDSS] score 0-2.5) were compared to 50 healthy controls using the Iowa Gambling Task (IGT). RESULTS: The performance of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
1
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 37 publications
3
33
1
4
Order By: Relevance
“…While DM can be preserved in very early RRMS patients [15], we found by means of a two-year follow-up study that such abilities rapidly declined over time, independently of other disease-evolution markers [7]. All these results underscore the fact that MS patients may fail in choosing advantageously when confronted with ambiguous situations.…”
Section: Introductionmentioning
confidence: 51%
“…While DM can be preserved in very early RRMS patients [15], we found by means of a two-year follow-up study that such abilities rapidly declined over time, independently of other disease-evolution markers [7]. All these results underscore the fact that MS patients may fail in choosing advantageously when confronted with ambiguous situations.…”
Section: Introductionmentioning
confidence: 51%
“…This approach has yielded marginal or non-significant results. For example, comparing multiple sclerosis patients with normal or weak decision-making ability, the difference in total score on a French version of the ISPC (Juillerat, Peter-Favre, & Van der Linden, 1998) was not significant (Simioni et al, 2008). In a second study, patients with multiple sclerosis did not differ from controls in total ISPC score, although there were differences in particular characteristics such as lack of stamina, inflexibility, social withdrawal and lack of insight (Souza Lima et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The ISPC has shown sensitivity to personality changes in patients with Parkinson's disease (Gronchi-Perrin et al, 2007; Houeto et al, 2002, 2006; Witjas et al, 2005), frontotemporal dementia (Hallam, MacKenzie, & Feldman, 2006), multiple sclerosis (Simioni et al, 2008, 2009; Souza Lima et al, 2007), brain cancer (Gleason, 2004), traumatic brain injury (Cantagallo, Contini, & Bianchi, 2010; Rochat, Ammann, Mayer, Annoni, & Van der Linden, 2009), focal vmPFC lesions (Driscoll, 2009; Koenigs et al, 2007; Tranel, Damasio, Denburg, & Bechara, 2005; Young et al, 2010), focal posterior lesions from stroke (Annoni, Devuyst, Carota, Bruggimann, & Bogousslavsky, 2005; Hommel et al, 2000), and temporal lobectomy (Sellal et al, 2003; Tranel & Bechara, 2009). However, the factor structure of the ISPC has not been investigated.…”
mentioning
confidence: 99%
“…Specifically, executive functions such as working memory, problem solving, abstract reasoning, planning, and inhibitory control, are often impaired (Arnett et al, 1997;Foong et al, 1997). Several behavioral studies using the IGT have reported DM impairment in patients with MS (Nagy et al, 2006;Roca et al, 2008;Simioni et al, 2008Simioni et al, , 2009Garc ıa-Molina et al, 2009). The execution of the IGT by patients with MS is characterized by a marked tendency to make unfavorable choices in comparison to healthy control subjects (Kleeberg et al, 2004;Nagy et al, 2006;Roca et al, 2008;Garc ıa-Molina et al, 2009;Simioni et al, 2009).…”
Section: Introductionmentioning
confidence: 99%